IMPLEMENTASI MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS SDM DI SMPN 03 MUNJUL KABUPATEN PANDEGELANG PROVINSI BANTEN - Julaeha, Eha (UNISAN JURNAL, 2024)
This study aims to determine the quality of human resources and to find out how efforts to improve the quality of human resources. This study uses a qualitative approach. While the method used in this research is descriptive research method. The data collection technique used is observation, interview and documentation techniques. This participatory observation technique is carried out to observe the geographic location in the form of a location plan and environmental conditions, vision, mission, strategy and motto of the school as well as the condition of human resources at SMPN 03 Munjul. Interviews were conducted to determine the stages of curriculum development. The quality of human resources (HR) at SMPN 03 Munjul, Kalidoni District, Palembang City is quite good, but still needs to be developed and improved. This is because the discipline of teachers and employees is still lacking, in terms of placement/distribution of subjects in this school there are still many teachers who hold subjects that are not in accordance with their respective faculties/fields. In making efforts to increase the productivity of SMPN 03 Munjul employees, Kali Doni District, Palembang City, it relies on direct guidance and supervision from the school principal/supervision in the form of administrative briefings, assessments and absences. Increasing the salaries of teachers and employees, fostering a sense of togetherness in realizing the mission and goals of both fellow teachers/employees and collaboration with the Foundation to jointly increase the productivity of teachers and school employees.